2001
DOI: 10.1055/s-2001-19005
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic vs. Conventional Vein Harvesting:First Results with a New, Non-Disposable System

Abstract: We conclude that the used endoscopic vein harvesting is a safe and cost effective method that can significantly reduce wound complications. An ongoing prospective study should establish our demonstrated data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Eight studies reported the incidence of post-operative oedema [4,16,21,25,30,32,33,37], with six of these showing a statistically significant reduction with MIVH as compared to the CVH group. Only three of these studies were randomised [4,16,21], with meta-analysis showing a significant reduction in oedema between MIVH (7/90) and CVH groups (30/60) with an odds ratio of 0.06 (CI 0.01-0.36).…”
Section: Meta-analysis Of Oedema Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Eight studies reported the incidence of post-operative oedema [4,16,21,25,30,32,33,37], with six of these showing a statistically significant reduction with MIVH as compared to the CVH group. Only three of these studies were randomised [4,16,21], with meta-analysis showing a significant reduction in oedema between MIVH (7/90) and CVH groups (30/60) with an odds ratio of 0.06 (CI 0.01-0.36).…”
Section: Meta-analysis Of Oedema Resultsmentioning
confidence: 96%
“…Overall, 22 of the studies reported the incidence of post-operative haematoma [4][5][6][15][16][17][18][19][20][21][22][23][24][25][26][28][29][30][31][32][33]37], with seven of these showing a statistically significant reduction in the MIVH as compared to the CVH group. Eleven of the studies were randomised [4][5][6][15][16][17][18][19][20][21][22], with metaanalysis of these calculating an incidence of haematoma of 53/676 (8%) in MIVH and 93/610 (15%) in CVH groups, with an odds ratio (OR) of 0.43 and confidence interval (CI) of 0.23-0.79, suggesting that this difference is statistically significant.…”
Section: Meta-analysis Of Haematoma Resultsmentioning
confidence: 99%
“…Few studies reported on patient satisfaction. 20,40,41,45,101 Patients' satisfaction with pain relief during hospitalization was significantly improved with EVH compared with OVH (MD = 1.88 points, 95% CI = 1.49 to 2.28, 1 study, 144 patients) but was no longer significant at 6-week follow-up (MD = 0.24 points, 95% CI = −0.09 to 0.57, P < 0.00001). Patient satisfaction with ambulation at hospital discharge was significantly improved with EVH compared with OVH (MD = 2.40, 95% CI = 2.02 to 2.75, 1 study, 144 patients, P < 0.00001).…”
Section: Patient Satisfaction Evh Versus Ovhmentioning
confidence: 97%
“…Several authors have published data on pain or mobility after vein harvesting; however, few authors have published information on both from the same population. 12,[15][16][17][18][19][20] To calculate postoperative utility, we chose to use estimates from Kiaii and colleagues 12 for 3 reasons: (1) it is a recent study; (2) this study is a prospective, randomized controlled trial; and (3) in this study the authors used the same method for quantifying postoperative mobility restriction and pain, a Likert Visual Analogue Scale (VAS). Assuming that VAS scores were normally distributed, the mean and standard deviation VAS scores at discharge and 6 weeks postoperatively were converted to a set of discrete scores between 0 and 3.…”
Section: Calculation Of Incremental Effectsmentioning
confidence: 99%
“…First, the great saphenous vein is the most frequently used conduit during this commonly performed operation, 1,23 and there is considerable morbidity associated with harvesting of the great saphenous vein. 12,[15][16][17][18][19][20] Furthermore, unless the increased clinical effectiveness of an intervention can be shown to justify its incremental cost, then policymakers have no incentive to allocate resources for its widespread adoption. 10,11 Finally, minimally invasive conduit harvesting techniques have the potential to be more widely applied.…”
Section: Implications For Practicementioning
confidence: 99%